Introducing security aspects with model transformation - FOX, JORGE; Jurjens, Jan (IEEE Computer Society, 2005)
Aspect Oriented Programming and subsequently Aspect Oriented Software Development have received great attention recently and constitutes an interesting field of research in computer science. The goal of this paper is to propose a more precise understanding of aspects based on the idea of crosscutting concerns in view of model transformation. This proposal considers security aspects as an example of a behavior applied over a desired software product. This implies improving the actual definition of aspects. The work introduces the main current concepts of aspect, defines aspects as behavioral entities, presents examples, and outlines a method for model transformation based on the proposed definition.
PUBLISHED
Keywords: aspect oriented programming; software development